2020
DOI: 10.3389/fped.2020.00485
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Delayed Neurodevelopment in Infants Using Brainstem Auditory Evoked Potentials and the Bayley II Scales

Abstract: Background: Brainstem auditory evoked potentials (BAEP) provide an objective analysis of central nervous system function and development in infants. This study proposed to examine the relationship between infant BAEP values at age 6 months, and their neurodevelopment at age 2 years assessed by the mental development indices (MDI), a form of Bayley Scales of Infant Development. We hypothesized that in infants with BAEP values outside normal range, there may be neurodevelopmental delays, as shown by their MDI sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
5
1
1
Order By: Relevance
“…The P-value for AEP wave three was 0.052, indicating a relatively closer statistical signi cance compared with the other SEP and VEP measures. A previous study by Wang et al demonstrated a strong association between AEP and neurodevelopmental outcomes in preterm infants using the Bayley Scale [24].…”
Section: Discussionmentioning
confidence: 94%
“…The P-value for AEP wave three was 0.052, indicating a relatively closer statistical signi cance compared with the other SEP and VEP measures. A previous study by Wang et al demonstrated a strong association between AEP and neurodevelopmental outcomes in preterm infants using the Bayley Scale [24].…”
Section: Discussionmentioning
confidence: 94%
“…But few studies have tested the relationship between hearing loss and the diagnostic rate of DD/ID. Hearing evaluation through subjective tests is difficult in young and uncooperative children, BAEP is reliable and effective tool in this setting [ 35 37 ]. Lau WL et al had found the prevalence of hearing deficit in children with Down syndrome in Hong Kong was 36% (18/55) measured by BAEP [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lau WL et al had found the prevalence of hearing deficit in children with Down syndrome in Hong Kong was 36% (18/55) measured by BAEP [ 35 ]. BAEP is also used to assess neuronal maturation [ 37 , 38 ]. In our study, 69 children (97.18%) were identified having hearing loss by BAEP and most children had a mild bilateral lesion (Supplementary Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Parental education was assigned as being either compulsory education (<9 years, low level), high school education (9–12 years, middle level), or some college/advanced training (>12 years, high level; du Prel Carroll et al, 2012). Household income was defined as <3000 Yuan/month, 3000–5999 Yuan/month, and ≥6000 Yuan/month three levels, in which 1.00 USD was equal to 6.23 RMB (Yuan) in 2015 (Wang et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…If the infants were unable to sleep, our clinicians would give a mild, calming chloral hydrate enema to the infants for BAEP recordings. As previously detailed (Wang et al, 2020), the recording electrode was placed in the midline of the forehead, and the reference electrode was placed at the bilateral mastoid. Electrode impedance was reduced to <5 kΩ, which was maintained during the session of BAEP recording.…”
Section: Methodsmentioning
confidence: 99%